KONTROL SISTEM STARTER SEPEDA MOTOR BERBASIS MIKROKONTROLER DENGAN SMARTPHONE ANDROID - Haydar Kurni; Dede Sunandar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The tool can be used in designing microcontrollers. Microcontrollers are small control devices that can be operated in conjunction with other electronic devices. The advantage of microcontrollers is that they can be used as a control system. Additionally, there are many non-open-source microcontroller boards available, making it difficult to create a control system. Bluetooth is a commonly used tool for electronic devices used for communication.